Fish-spearing off Point Baleine, Trinidad - (:unkn) unknown (F.P. Bruce-Austin,[Trinidad and Tobago], 2011)
The postcard shows a man spear fishing from a small boat off Point Baleine, Gasparee Island, Trinidad. Point Baleine thrived as a whaling station around the year 1900.
Colour: Sepia; Style: Landscape; Other: Bordered, Divided
Keywords: Trinidad and Tobago; Postcards; Fishing--Trinidad and Tobago; Fishing boats--Trinidad and Tobago; Men--Trinidad and Tobago; Gasparee; Gaspar Grande